Nothing but trouble - Kamen, Michael 1948-2003 (Shout! Factory, 2021)
A ghoulish comedy wherein a wrong turn sends two yuppies into Valkenvania, the Twilight Zone of speed traps
Orig.: USA, 1991
1080p High-Definition Widescreen (1.85:1)
Keywords: Comedy films; Filmkomödie; Yuppies / Drama; Speed traps / Drama; DVD-Video discs; Speed traps; Video recordings; Yuppies; Drama; Feature films; Fiction films; Films for the hearing impaired; Video recordings for the hearing impaired; Films comiques; Films de fiction; Films pour personnes handicapées auditives; Vidéos pour personnes handicapées auditives; Vidéos; Film; Blu-Ray-Disc